A new perspective on the functioning of the brain and the mechanisms behind conscious processes - Keppler, Joachim (Frontiers in Psychology, 2013)
An essential prerequisite for the development of a theory of consciousness is the clarification of the fundamental mechanisms underlying conscious processes. In this article I present an approach that sheds new light on these mechanisms. This approach builds on stochastic electrodynamics (SED), a promising theoretical framework that provides a deeper understanding of quantum systems and reveals the origin of quantum phenomena. I outline the most important concepts and findings of SED and interpret the neurophysiological body of evidence in the context of these findings, indicating that the functioning of the brain rests upon exactly the same principles that are characteristic for quantum systems. On this basis, I construct a new hypothesis on the mechanisms behind conscious processes and discuss the new perspectives this hypothesis opens up for consciousness research. In particular, it offers the possibility of elucidating the relationship between brain and consciousness, of specifying the connection between consciousness and information, and of answering the question of what distinguishes conscious processes from unconscious processes.